Behavioral effects of social challenges and genomic mechanisms of social priming: What's testosterone got to do with it?. Issue 6 (1st December 2014) - Rosvall, Kimberly A.; Peterson, Mark P.
Abstract: Social challenges from rival conspecifics are common in the lives of animals, and changes in an animal's social environment can influence physiology and behavior in ways that appear to be adaptive in the face of continued social instability (i.e. social priming). Recently, it has become clear that testosterone, long thought to be the primary mediator of these effects, may not always change in response to social challenges, an observation that highlights gaps in our understanding of the proximate mechanisms by which animals respond to their social environment. Here, our goal is to address the degree to which testosterone mediates organismal responses to social cues. To this end, we review the behavioral and physiological consequences of social challenges, as well as their underlying hormonal and gene regulatory mechanisms. We also present a new case study from a wild songbird, the dark-eyed junco Junco hyemalis, in which we find largely divergent genome-wide transcriptional changes induced by social challenges and testosterone, respectively, in muscle and liver tissue. Our review underscores the diversity of mechanisms that link the dynamic social environment with an organisms' genomic, hormonal, and behavioral state. This diversity among species, and even among tissues within an organism, reveals new insights into the pattern and process by which evolution may alter proximate mechanisms of social priming.